ANALYSIS OF FACTORS AFFECTING THE PERFORMANCE OF POSBINDU NON-COMMUNICABLE DISEASES - Suciatmi, Ika; Arwani; Widiyanto, Budi (Syntax Corporation Indonesia, 2024)
The cause of death of approximately 71% (36 million) people per year is due to non-communicable diseases. The 2018 Riskesdas data shows an increase in key NCD indicators. The significant increase in NCDs is expected to add to the burden on both the public and the government in healthcare financing. According to Government Regulation No. 71 of 2015, the prevention and control of NCDs are to be carried out through community health efforts and individual health efforts. The prevention and control of NCDs in the community are implemented through the activities of the NCD Posbindu. This research analyzes the factors affecting the performance of NCD Posbindu. The research method used is a Cross-Sectional approach with a quantitative method. The population consists of 486 NCD Posbindu, and the research sample uses Total Sampling, consisting of 29 NCD Posbindu. Data analysis includes univariate, bivariate (Spearman Rank), and multivariate (Multiple Linear Regression). The research results show that the majority of NCD Posbindu's performance falls into the